Age-dependent effect of vitamin D supplementation on musculoskeletal health in chronic spinal cord injury patients: A pilot study - Yang, Hea-Eun; Lee, Byeong Wook; Choi, I. Jun; Oh, Ji Yeon; An, Eui Jin (The journal of spinal cord medicine, 2025)
To determine the effect of vitamin D supplementation on changes in body composition associated with musculoskeletal health status in patients with chronic SCI and vitamin D deficiency as a response to age. Prospective drug-intervention study. Department of rehabilitation medicine, Veterans Health Service Medical Center. Seventeen patients with vitamin D insufficiency/deficiency (<30 ng/mL) and chronic SCI were divided into two groups: groups A <65 years ( = 8) and B ≥65 years of age ( = 9). Both groups received 800 IU/day cholecalciferol for 12 weeks. We used blood samples to evaluate metabolites related to vitamin D, testosterone (T), lipid profiles, and sex hormone-binding globulin (SHBG). Bioelectrical impedance analysis (BIA) was used to evaluate body composition. Group A had significantly better baseline clinical characteristics for all BIA measurements. SHGB was significantly higher in Group B ( = 0.003) and albumin was significantly higher in Group A ( = 0.000). When comparing pre- to post-treatment, Group A showed a significant improvement in T ( = 0.042), total cholesterol ( = 0.035), and triglyceride ( = 0.025) levels, whereas Group B significantly increased vitamin D ( = 0.038) and protein mass (PM) ( = 0.034) levels. This study suggested that addressing vitamin D deficiency in patients with SCI had different effects in young and older adults, with both groups showing positive changes in body composition. Particularly, the increase in PM on BIA measurements in elderly patients at high risk of sarcopenia was encouraging.